2014
DOI: 10.1002/qua.24815
|View full text |Cite
|
Sign up to set email alerts
|

Potential generation and path‐integral Monte Carlo in study of microscopic superfluidity

Abstract: The idea of a macroscopic Andronikashvili experiment used to measure superfluid fraction of bulk liquid 4 He can be ported into the realm of spectroscopic studies to measure the superfluid fraction of microscopic systems at the nanoscale. Theoretical studies are needed to fully unravel the superfluid information contained in such a microscopic Andronikashvili experiment. Two aspects of the theoretical studies, the generation of accurate and efficient potential energy surfaces, and the methodology of path-integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
(165 reference statements)
0
1
0
Order By: Relevance
“…The study of hydrogen clusters has been the subject of much research in both theory and experiment, a key reason being that superfluid properties of parahydrogen have been observed at low temperatures. , In 1972, Ginzburg and Sobyanin started the discussion, suggesting that pH 2 may be a superfluid and proposed several ways to observe it. The next major theoretical breakthrough was in 1991, as Sindzingre et al calculated the superfluid fractions of pH 2 clusters using the Path Integral Monte Carlo (PIMC) method and observed that, below 2 K, (pH 2 ) 13 and (pH 2 ) 18 were superfluid, but (pH 2 ) 33 remained nonsuperfluid.…”
Section: Introductionmentioning
confidence: 99%
“…The study of hydrogen clusters has been the subject of much research in both theory and experiment, a key reason being that superfluid properties of parahydrogen have been observed at low temperatures. , In 1972, Ginzburg and Sobyanin started the discussion, suggesting that pH 2 may be a superfluid and proposed several ways to observe it. The next major theoretical breakthrough was in 1991, as Sindzingre et al calculated the superfluid fractions of pH 2 clusters using the Path Integral Monte Carlo (PIMC) method and observed that, below 2 K, (pH 2 ) 13 and (pH 2 ) 18 were superfluid, but (pH 2 ) 33 remained nonsuperfluid.…”
Section: Introductionmentioning
confidence: 99%